057 Proteomic analysis of TDP-43 pathology in frontotemporal dementia. Issue 12 (14th November 2019) - Shafei, Rachelle; Toomey, Christina; Foiani, Martha; Mills, Kevin; Lashley, Tammaryn; Rohrer, Jonathan
Abstract : Introduction: Frontotemporal dementia (FTD) is a heterogeneous neurodegenerative disorder presenting with behavioural or speech problems. Identification of the underlying molecular abnormality during life remains elusive, and there are no reliable biomarkers of TDP-43 proteinopathies. Proteomic analysis of the TDP-43 proteinopathies provides a unique opportunity to better understand the disease-associated pathways and determine surrogate biomarkers of TDP-43 pathology. Materials and methods: We set out to investigate the proteomic profile of TDP-43 proteinopathies using label-free quantitative mass spectrometry. 15 cases were selected: 9 had histologically confirmed TDP-43 inclusions as their primary pathology, 3 had Alzheimer's disease (AD) pathology (without TDP-43 disease) and 3 were healthy controls. Three regions from each case were examined: frontal lobe, temporal lobe and hippocampus. Samples were pooled according to pathological group and brain region before mass spectrometric analysis (Synapt G2-Si nanoAcquity LC system). Results: 21 proteins were significantly upregulated in TDP-43 proteinopathies compared with AD and 30 proteins were downregulated. The majority of proteins identified are implicated in ribosomal function, RNA transportation and mitochondrial matrix enzymatic function. Whilst, several proteins identified have already been shown to be implicated pathophysiologically in FTD/ALS the majority have not, providing a new insight into disease pathogenesis. Discussion: Preliminary proteomic analyses of brain tissue from TDP-43 proteinopathies has identified a number of differentially expressed proteins, providing a starting point for new biomarker development to distinguish different pathological subtypes of FTD during life.